Rehabilitation of Grade IV Knee Osteoarthritis With Genu Valgum in an Obese Female Patient: A Case Report - Hasyim, Mega Elisa (Plexus Medical Journal, 2025)
Background: Knee osteoarthritis (OA) is a common degenerative joint disease that affects weight-bearing joints and impairs mobility, especially among the elderly. Risk factors include aging, obesity, and malalignment. In severe cases, Total Knee Replacement (TKR) is often recommended, but not all patients are psychologically ready for surgery. Case Presentation: We report a case of a 57-year-old obese woman (BMI 34.2 kg/m²) diagnosed with bilateral grade IV knee OA and genu valgus deformity. She presented with progressive bilateral knee pain, stiffness, and functional decline. Despite being scheduled for TKR, she refused surgery due to psychological unpreparedness. Her history included controlled congestive heart failure (CHF). Radiographic evaluation confirmed advanced OA with femoropatellar involvement and quadriceps tendon enthesopathy. Her Barthel Index was 85/100. A multidisciplinary conservative rehabilitation program was initiated, including short-wave diathermy, active and progressive strengthening exercises, aerobic training, knee bracing, and joint protection education. Pharmacologic therapy was tailored to her CHF. Nutritional counseling focused on caloric reduction, balanced intake, and gradual weight loss. After four months, the patient reported pain reduction (VAS from 6 to 2), improved joint mobility, and regained functional independence. She also experienced a 4 kg weight loss, which contributed to reduced joint stress and enhanced gait performance. No CHF-related complications were noted, and adherence to brace use improved with consistent education. Conclusion: This case underscores the value of individualized multidisciplinary rehabilitation for advanced knee OA, particularly in patients with comorbidities and delayed surgical readiness. Conservative treatment may serve as an effective patient-centered alternative to surgery.